Effect of castor leaves supplemented with seed flours of soybean, cowpea and amaranthus on larval and cocoon parameters of eri-silkworms (Samia cynthia ricini) - Taye, Beshada; Terefe, Metasebia; Shifa, Kedir; Tsegaw, Aynalem; Tilahun, Abiy; Ibrahim, Ahmed (Ethiopian Journal of Science and Technology, 2025)
The growth, development, and silk yield of silkworms are highly affected by the quality of the leaves used as feed. In the present investigation, eri silkworms were fed flour supplements made from soybean (Glycine sp.), cowpea (Vigna sp.), and Amaranthus (Amaranthus sp.) seeds at concentration levels of 45 g/kg, 30 g/kg, and 15 g/kg of castor leaf, respectively. A control group was included with castor leaves and no supplementation. The experiment, comprising ten treatments, was laid out in a completely randomized design (CRD) with five replications at the Melkassa Agricultural Research Center (MARC) in the East Shewa Zone of Oromia Regional State, Ethiopia. The treatments were evaluated for their effects on important larval and cocoon parameters of eri silkworms (Samia cynthia ricini B.) using a white plain Eri silkworm breed known as Eri-3.4. Data analysis was conducted using SAS software at a 5% probability level. The treatment combinations showed significant differences among themselves, and the addition of leaf supplements in powder form improved various larval and cocoon parameters, including larval weight, effective rate of rearing, cocoon weight, pupal weight, shell weight, and shell ratio. Among the treatments, soybean at a rate of 45 g/kg of castor leaf and 30 g/kg of castor leaf, cowpea at 45 g/kg of castor leaf, and Amaranthus at 45 g/kg of castor leaf were found to be superior, yielding better results in terms of larval and cocoon parameters. Therefore, it can be concluded that applying powders made from the seeds of soybean, cowpea, and Amaranthus on castor leaves improves eri silkworm parameters and can be considered as basic inputs for supplementary feed in future silkworm rearing.